Synthesis of Gray codes - Білецький, А. Я.; Біленький, О. А. (Proceedings of National Aviation University (archive), 2002)
The algorithms and structural schemes of the formation of the left-hand and right-side Gray codes in binary and t-th systems of calculation are given.